Wiara w pismach Afrahata - Uciecha, Andrzej (Vox Patrum, 2014)
The issue of faith forms the cornerstone of Aphrahat’s ascetic teaching, and it is dealt with in all the Demonstrations. The order and logical coherence of the topics discussed in the first homily, De Fide, particularly in the articles of Aphrahat’s Credo and the Letter of an Inquirer, as well as in the other Demonstrations, are clear and obvious only to someone who believes in the one and only God. The Persian sage elaborates the thought that the edifice of faith is built upon Christ who is its only foundation and, at the same time, its only head of the wall. The author employs the existing biblical tradition, giving a Christocentric interpretation to the narration taken from the Book of Isaiah (cf. Is 50, 7). The works of faith, quoted in the form of biblical testimonia, which are typical of Aphrahat, cover the entire work of creation and demonstrate the greatness and the divine wisdom of the Creator acting throughout the history of salvation.